Entangled histories of the Balkans
1 online resource.
Keywords: Modern Balkan history has traditionally been studied by national historians in terms of separate national histories taking place within bounded state territories. The authors in this volume take a different approach. They all seek to treat the modern history of the region from a transnational and relational perspective in terms of shared and connected, as well as entangled, histories, transfers and crossings. This goes along with an interest in the way ideas, institutions and techniques were selected, transferred and adapted to Balkan conditions and how they interacted with those conditions, resulting in mélanges and hybridization. The volume also invites reflection on the interacting entities in the very process of their creation and consecutive transformations rather than taking them as givens. Contributors include: Diana Mishkova, Alexander Vezenkov, Constantin Iordachi, Roumen Daskalov, Tchavdar Marinov, Blagovest Njagulov.